TRAINING OF KEFIR DRINK MAKING FOR DAIRY GOAT`S AND COW`S BREEDER IN PURWOSARI, LAMPUNG TIMUR - nurul fajrih; ANHAR FAISAL (INTASTAWIT Journal (Indonesian Tasamuh, Tawassuth, I'tidal, dan Tawazun), 2020)
Milk is a foodstuff that is very important for human life. This fact had been known by people since b.c. years ago that milk could support human growth very well since infant until adult age. Cow`s Milk and Goat`s Milk produced by farmer/breeder group in the village only being traded as fresh milk without any alternative to process it to be other processed product. Even less if produced milk was very abundant, it could not sold out and finally been wasted. It need to be quality improved, and be storage period extended, it need to be further processed be kefir drink. Problems happened was lack of knowledge about benefits of drinking milk especially Kefir drink because of no information about familiarization or promotion to Purwosari Community. Beside that, any worry about its taste and smell did not quite right with Indonesian people taste. Therefore, people need to be introduced and educated about Kefir production from Goat `s and Cow`s milk. The expectation of this activity to create increase of milk consumption in Kefir drink form especially in Purwosari Village. The conclusion of this community dedication is the increase of knowledge and education Purwosari community about plan and produce milk and community skill in making Kefir drink.